A phagostimulant based bait composition for tobacco caterpillar Spodoptera Litura (Fabricius) (Lepidoptera: Noctuidae) - Shahanaz, M. R.; Pathrose, Berin; Chellappan, Mani (Journal of Tropical Agriculture, 2019)
Laboratory studies were conducted during 2017-2018 at the Department of Agricultural Entomology, College of Horticulture, Vellanikkara, Kerala Agricultural University, Thrissur, to evaluate different base materials and a phagostimulant, which could serve as baits for Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae). Baits were prepared using different bran materials such as rice bran, maize bran and wheat bran, along with jaggery and water. Mean consumption of bait by six-day old S. litura larvae after 48h revealed superiority of wheat bran (4:1:4 ratio), followed by maize bran. Addition of phagostimulants such as corn starch and coconut oil were found to increase the consumption of bait. The bait composition identified would be extremely helpful in preparing insecticide based poison baits for the management of S. litura.